Kunaung Njik Kileng: Analisis Fungsi Vladimir Propp - Mahawitra Jayawardana; Silvia Rosa (Jurnal Bahasa dan Sastra, 2021)
This paper aims to discuss the kunaung Njik Kileng that developed in Kerinci to reveal the 31 functions of Vladimir Propp's narrative structure. This research is a qualitative research with descriptive method. The data in this study were transcription of kunaung Njik Kileng which is contained in the book Struktur Sastra Lisan Kerinci.. Data analysis was carried out by classifying the data according to the Propp function, analyzing the function of the story, describing the story scheme based on the results obtained from the function analysis, and distributing it into the action environment contained in the story. The results of this study concluded that there were 14 of the 31 functions according to Vladimir Propp. This kunaung also has an advanced plot after analyzing the story patterns contained in this kunaung. There are several characters who have the character of villains, donors, and even heroes. In addition, this kunaung contains messages to carry out duties and responsibilities in the family which are represented by the functions contained in the ancient text.